The legal history of animal protection in the United States - Favre, David S. (Animals as crime victims, 2024)
The question of whether an animal can be considered to be a victim in the world of criminal law must first consider how animals are historically and presently considered generally in the criminal justice system. The last 200 years of American history has seen a significant shift in how humans view the animals around them. Initially they were just property having only economic value, but then the law acknowledged their capacity for pain and suffering and sought to ameliorate unnecessary inflictions. However, they remained property and this status continues today. Animal protection laws are now robust for some groups of animals such as companion animals, but less protected for those animals within industrial agriculture. Some animals are on the threshold of obtaining victim status. Obtaining this status will clearly move them out of the box of personal property to a new level of acknowledgement within the legal system.